Pengaruh Model Pembelajaran Contextual Teaching And Learning (CTL) Menggunakan Media Kartu Kata Bergambar Terhadap Hasil Belajar IPA Siswa Kelas IV SD Negeri 4 Motui - Ica Yunarni Ningsi; Chairan Zibar L. Parisu; La Sisi (Journal of Humanities, Social Sciences, and Education, 2025)
The purpose of this study is to determine the effect of the Contextual Teaching and Learning (CTL) model using picture word card media on students' learning outcomes. This study employs a quantitative research method with a pre-experimental design, specifically the One-Group Pretest-Posttest Design. The results show that prior to the treatment, out of 20 students, 9 students (45%) achieved the minimum passing grade, while 11 students (55%) did not. The average pretest score was 66.20, categorized as low. After the treatment, 15 students (75%) met the minimum passing grade, and 5 students (25%) did not. The average posttest score increased to 77.00, categorized as high. Inferential statistical analysis using the t-test formula revealed a significant difference between the pretest and posttest results, with a significance value (2-tailed) of 0.003 < 0.05. This indicates a significant improvement in science learning outcomes between the pretest and posttest data.